W-shaped Recovery in the Two Waves of the Coronavirus Pandemic - Molnár, Dániel; Horváth, Diána; Regős, Gábor (Public Finance Quarterly, 2021)
Our study aims to examine what course the coronavirus crisis took in certain areas, using macroeconomic data and a household and business survey. Our results suggest that the virus has affected different sectors to varying degrees: while some sectors have experienced rapid recovery, others have been characterised by a protracted crisis. The second wave of the coronavirus in the autumn also resulted in a decline in economic data, but to a lesser extent than the first wave in the spring. Overall, the course of the crisis can be considered W-shaped, although some aspects and sectors show a different picture. However, as the viral situation improves, it will be an important task of economic policy to ensure that the last stem of the W is steep, i.e. that the Hungarian economy can return to its previous growth trajectory. To this end, it is essential to lift restrictions, so that household consumption can once again become the engine of growth, and to increase the willingness of companies to invest.